Des parents en quête de parentalité - Séverine Euillet; Chantal Zaouche-Gaudron (Sociétés et Jeunesses en Difficulté)
Parents searching for parenthood. The example of parents whose children have been taken into care     For more than a decade, the notion of parenthood has been used in numerous public and social areas including child protection. Child foster care cases are thus currently analysed by professionals within the frame of this notion of parenthood and the definitions and representations that are associated with it.What is the identity of parents whose child has been taken into care by another family? A research conducted with 24 parents underlines their feelings of worthlessness and how they suffer from the feeling of being viewed as bad parents. Even if 65 % say that they have a good relationship with social services, only 4 % believe that the social services see them as good parents. Suffering felt by parents regarding their parental identity is linked to the feeling of being perceived negatively by social services, which taints the relationship between parents and professionals and consequently impedes eventual support actions for parenthood